2019
DOI: 10.1080/21691401.2018.1553783
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a-5p frequently downregulated in prostate cancer inhibits cell proliferation via targeting PCLAF

Abstract: MicroRNAs (miRNAs) have vastly expanded our view of RNA world in intracellular signal regulating networks. Here, we functionally characterized a normally highly expressed miRNA, miR-30a-5p (MIMAT0000087), which exhibits downregulated expression profiles in prostate cancer samples. MiR-30a-5p knockdown and overexpression in PC-3 cell line alters cell proliferation supporting a tumour suppressor role. We also discovered that PCLAF is the direct target of miR-30a-5p. Notably, PC-3 cell proliferation is inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
(36 reference statements)
4
30
0
Order By: Relevance
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 . miR‐30a inhibits proliferation, 15,16 invasion and epithelial‐mesenchymal transition of PCa cells 12,41 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 . miR‐30a inhibits proliferation, 15,16 invasion and epithelial‐mesenchymal transition of PCa cells 12,41 .…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we and others have shown that the aberrant expression of miR‐30a is associated with epithelial‐mesenchymal transition, radiosensitivity, proliferation, and invasion in PCa 12‐16 . To the best of our knowledge, the role of miR‐30a in CRPC has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 93%
“…Currently, the expression profile and function of miR-30a-5p in different malignancies are still existed controversies. A large number of reports have demonstrated that miR-30a-5p was commonly down-expression and regulated biological behaviors of tumor growth, invasion, epithelial-mesenchymal transition (EMT) in various types of cancers [13,14,18]. miR-30a-5p was down-regulated in prostate cancer and inhibited cell proliferation via targeting PCLAF [14].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports have demonstrated that miR-30a-5p was commonly down-expression and regulated biological behaviors of tumor growth, invasion, epithelial-mesenchymal transition (EMT) in various types of cancers [13,14,18]. miR-30a-5p was down-regulated in prostate cancer and inhibited cell proliferation via targeting PCLAF [14]. Furthermore, the down-regulation of miR-30a-5p was associated with poor prognosis and promoted chemoresistance of gemcitabine in pancreatic ductal adenocarcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation